Raising calves - a strategic investment for smallholder farmers in East Africa - Ojango, Julie M.K. (International Livestock Research Institute, 2022)
This presentation by Dr Julie Ojango, senior scientist at ILRI, featured at the International Dairy Federation webinar on 24/02/22.